Women's experiences of psychological treatment and psychosocial interventions for postpartum depression: a qualitative systematic review and meta-synthesis - Pamela Massoudi; Leif A. Strömwall; Johan Åhlen; Maja Kärrman Fredriksson; Anna Dencker; Ewa Andersson (BMC, 2023)
Abstract Background To provide a comprehensive, systematic evaluation of the literature on experiences of psychological interventions for postpartum depression (PPD) in women. Depression is one of the most common postpartum mental disorders. Studies have identified that psychological interventions reduce depressive symptoms. However, less is known about the experiences of women who have received such treatments. Methods A systematic review of the literature was conducted by searching five databases (CINAHL, Cochrane Library, EMBASE, Medline, PsycINFO), in August 2022. Studies with qualitative methodology examining women's experiences of professional treatment for PPD were included and checked for methodological quality. Eight studies (total N = 255) contributed to the findings, which were synthesized using thematic synthesis. Confidence in the synthesized evidence was assessed with GRADE CERQual. Findings The women had received cognitive behavioral therapy (5 studies) or supportive home visits (3 studies). Treatments were individual or group-based. Two main themes were identified: Circumstances and expectations, and Experiences of treatment, with six descriptive themes. Establishing a good relationship to their health professional was important for the women, regardless of treatment model. They also expressed that they wanted to be able to choose the type and format of treatment. The women were satisfied with the support and treatment received and expressed that their emotional well-being had been improved as well as the relationship to their infant. Conclusion The findings can be helpful to develop and tailor patient-centered care for women who are experiencing postnatal depression.